Phosphotellurite glass and glass-ceramics with high TeO2 contents: Thermal, structural and optical properties - Manzani, Danilo; Souza Junior, João B.; Reyna, Albert S.; Silva Neto, Manoel L.; Bautista, Jessica E. Q.; Ribeiro, Sidney J. L. [UNESP]; De Araújo, Cid B. (Royal Society of Chemistry (RSC), 2019)
Phosphotellurite based glasses have interesting features such as low characteristic temperatures, high glass forming ability, high thermal stability against crystallization and a broad transparency window from ultraviolet (UV) to near-infrared (NIR), which makes them promising materials for photonic applications. In this work, phosphotellurite binary glasses, having a composition (100 - x)TeO2 - xBa(PO3)2 with x varying from 1 to 20 mol%, were synthesized by the conventional melt-quenching method in covered gold crucibles under air. Optical, physical and structural properties of the new glass samples were investigated by differential scanning calorimetry, X-ray diffraction, Raman spectroscopy, transmission electron microscopy, linear optical absorption from UV to NIR, IR transmittance, and optical limiting experiments. Transparent glass-ceramics in the visible range were obtained for phosphotellurite samples containing 2, 4 and 6 mol% of Ba(PO3)2 and the phase crystallization was investigated through Rietveld analysis and transmission electron microscopy. The incorporation of Ba(PO3)2 into the TeO2 network drastically increases the thermal stability against devitrification and helps to shift the infrared multiphonon absorption edge to longer wavelengths. Nonlinear measurements performed with a picosecond laser at 532 nm indicate large effective nonlinear absorption coefficients for all samples. In summary, the dependence of the spectroscopic properties on the compositions of the samples revealed promising transparent glass and glass-ceramics for photonic applications.